Blitar’s indigenous knowledge promotion through local content collections at Blitar Public Library - Yuni Pratiwi; Elok Rizki Khusnul Khotimah; Lidya Amalia Rahmania (Jurnal Kajian Informasi dan Perpustakaan, 2022)
The public library is one of the institutions that have the function and task of preserving indigenous knowledge. Recorded in the form of collections stored in the library's local content service consist of printed books, e-books, and audio-visual collections use social media, especially Instagram, can facilitate the dissemination of indigenous knowledge information to local content collections in public libraries. This study aimed to produce media to promote Blitar's indigenous knowledge in the form of infographics with information sourced from the local content collection at the Blitar Public Library. Research method used development method and the Four-D development model with product development stages consisting of defining, designing, developing, and distributing. Respondents in this study were the people of Blitar, media promotion experts, material experts, and expert practitioners (librarians). In this study, product trials were carried out on three aspects consist of material, visual, and language. Based on the trials and validity tests results, it concludes that Blitar's local content promotion media products in the form of infographics are suitable for use with revisions. Blitar local wisdom infographics increase the reach by maximizing the use of hashtags and scheduling infographic uploads at the best times. Local content promotion media products in infographics form produced in this development research are quite good.  However, there needs to be some improvement especially on material aspect.  The material that was carried did not represent all local wisdom topics in Blitar.